Systematization of nursing care for pregnant women in the obstetric surgical center: potentials and challenges (Research, Society and Development, 2022)
Objective: To investigate the scientific evidence on nursing care for pregnant women in the obstetric surgical center instrumented by the Nursing Process. Method: An integrative literature review was carried out by consulting the BDENF, LILACS and SciELO databases through the Virtual Health Library and SciELO's official website. Controlled and uncontrolled descriptors were used: operating room, pregnant woman, obstetric operating room, pregnancy, high-risk pregnancy, nursing process and systematization of nursing care. To formulate the search strategy, the descriptors were combined with each other using the Boolean operators AND and OR. Eligibility included primary studies, available online, in Portuguese and English, considering the time frame from 2016 to 2020, excluding theses, manuals, monographs, dissertations, editorials, clinical practice guides and reviews. Results: Six articles were selected that revealed that the nurse recognizes the importance of applying the nursing process, but alleges lack of time due to the work overload for its implementation. Final Considerations: a gap was perceived in the publications regarding the theme of applying the systematization of nursing care in the obstetric surgical center, a fact that corroborates the encouragement of future studies on the subject.